Two-dimensional quantum gravity with matter fields - Bittner, Elmar; Janke, Wolfhard; Markum, Harald; Riedler, Jürgen (Nuclear physics. Proceedings supplements, 2000)
We present a Monte Carlo study of the Ising model coupled to the fluctuating geometry of the two-dimensional Discrete Regge Model and compare the results with previous simulations employing Standard Regge Calculus. We perform a careful finite-size scaling analysis of the phase transition in the Ising model sector and report estimates of the associated critical exponents.